The structure of freight flows in Europe and its implications for EU railway freight policy - Kay Mitusch; Gernot Liedtke; Laurent Guihery; David Bälz (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
We analyse the potential for shifting freight transports to the railways in Western and Central Europe. This potential arises for large and concentrated freight flows over long distances of about 300 km or more. However, we show that there are only few such freight flows in Europe, and that they are concentrated or connected to the central European population centers, sometimes called the "Blue Banana". As a consequence, the European railway freight corridors according to EU Regulation 913/2010 should be divided into two distinct groups: first tier and second tier corridors. Substantial innovations should be introduced on the first tier corridors first, in order to increase efficiency and reduce noise. This refers to core innovations for rolling stock like the introduction of automatic couplings, electronic or electro-pneumatic brakes, and modern bogies.
urn:nbn:de:swb:90-431573
Keywords: R48; L92; Q55; 330; freight transport; railways; corridors; rolling stock; innovation policy